2022
DOI: 10.3389/fpsyg.2022.822234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Ventromedial Prefrontal Cortex in Preferential Decisions for Own- and Other-Age Faces

Abstract: Own-age bias is a well-known bias reflecting the effects of age, and its role has been demonstrated, particularly, in face recognition. However, it remains unclear whether an own-age bias exists in facial impression formation. In the present study, we used three datasets from two published and one unpublished functional magnetic resonance imaging (fMRI) study that employed the same pleasantness rating task with fMRI scanning and preferential choice task after the fMRI to investigate whether healthy young and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…The temporal pole has been associated with representations of specific knowledge, such as norms and values, about others and the world (Monticelli et al, 2021 ; Schurz et al, 2014 ). The vmPFC is related to thinking about similar others, and in processing our own preferences (Heleven & Van Overwalle, 2019 ; Ito et al, 2022 ; Mitchell et al, 2006 ; Van Overwalle, 2009 ) All these processes are involved in making predictions about other persons’ actions based on their preferences, such as imaging an adequate scene, knowing the boundaries set by social norms and values, and thinking about a persons’ inner preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal pole has been associated with representations of specific knowledge, such as norms and values, about others and the world (Monticelli et al, 2021 ; Schurz et al, 2014 ). The vmPFC is related to thinking about similar others, and in processing our own preferences (Heleven & Van Overwalle, 2019 ; Ito et al, 2022 ; Mitchell et al, 2006 ; Van Overwalle, 2009 ) All these processes are involved in making predictions about other persons’ actions based on their preferences, such as imaging an adequate scene, knowing the boundaries set by social norms and values, and thinking about a persons’ inner preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Most databases have young/middle-age models portrayed with direct gaze, but there are also available stimuli sets with models of different ages across lifespan ( Minear and Park, 2004 ; O’Reilly et al, 2016 ) and the FACES-database ( Ebner et al, 2010 ) included young, middle-age and older models posing six different emotions. Age is indeed a crucial dimension in face processing, it is linked with attractiveness ( Thornhill and Gangestad, 1999 ; Perrett et al, 2002 ) and face preference ( Ebner, 2008 ; Ito et al, 2022 ), it correlates with perceived height, masculinity and dominance ( Batres et al, 2015 ), and a same-age effect is reported for face recognition ( Bäckman, 1991 ); namely, better performances in recognizing individuals similar to own age. Moreover, a recent factor analysis carried out to model the structure of perception of personality traits from highly variable face stimuli ( Sutherland et al, 2013 ) resulted in a three-dimensional model with approachability, dominance and youthful-attractiveness as factors predicting face evaluation.…”
Section: Introductionmentioning
confidence: 99%